Prehistoric Population Change within the Mt. Trumbull, AZ, Area. Issue 4 (2nd October 2019) - Buck, Paul
Abstract : Recent archaeological research in the Mt. Trumbull region of northwestern Arizona has confirmed the presence of an unusually large number and variety of Virgin Branch Puebloan sites. Subsurface testing of a sample of these sites provides limited chronological controls using both radiocarbon and optically stimulated luminescence (OSL) dates on the occupations. Intensive survey of a large parcel of land has quintupled the number of sites known. Field mapping of the abundant structural sites in the area, coupled with random artifact surface collections, indicates rough ages for many of these sites. The unique abiotic characteristics of the Mt. Trumbull area allowed widespread settlement of the area perhaps as early as Basketmaker III times, followed by significant aggregation into larger C- and L- shaped pueblos towards the end of the Pueblo II and the early Pueblo III periods.